Improving Teacher-Student Collaboration And Educational Effectiveness By Overcoming Learning Challenges - Mullabayev Baxtiyarjon Bulturbayevich; Abdul Rahmat; Mallaboyev Nosirjon Murodullayevich (Aksara: Jurnal Ilmu Pendidikan Nonformal, 2021)
This article discusses the importance of lectures and practical lessons in students'learning activities, the difficulties encountered in learning and its causes, the forms of cooperation between teachers and students, and important factors in improving the effectiveness of education.